A Surgical Overview on Modified Alvarado Scoring - Dogra, Varun; Gilkar, Ishfaq Ahmad; ., Silvi (Issues and Developments in Medicine and Medical Research Vol. 2, 2022)
Vermiform appendix as the name defines is a narrow, worm-shaped tube which arises from the posteromedial wall of the caecum. Appendicitis is defined as an inflammation of the inner lining of the vermiform appendix that spreads to its other parts. Acute appendicitis is the most common surgical emergency in most Surgical Emergency Rooms. Arriving at the correct diagnosis is essential; however, a delay may allow progression to perforation and significantly increased morbidity and mortality. Methods advocated to assist in the diagnosis of appendicitis include scoring systems, ultrasonography, computer programs, computed tomography, magnetic resonance imaging and laparoscopy. Several scoring systems have been used globally for early diagnosis of acute appendicitis. One of the most practical scoring systems is the Alvarado scoring system which is based on history, physical examination, and some laboratory investigations that are convenient to apply Modified Alvarado Score has a decent Sensitivity, Specificity, Positive Predictive Value and Negative Predictive Value. Modified Alvarado and ultrasonography can be used together in surgical emergency for diagnosing cases of acute appendicitis.